Selective regulatory function of Socs3 in the formation of IL-17-secreting T cells - Chen, Zhi (National Academy of Sciences, 2006)
Suppressor of cytokine signaling (Socs) 3 is a cytokine-inducible inhibitor with critical but selective cell-specific effects. We show that deficiency of Socs3 in T cells had minimal effects on differentiation of T cells to the T helper (Th) 1 or Th2 subsets; accordingly, Socs3 had no effect on IL-12-dependent signal transducer and activator of transcription (Stat) 4 phosphorylation or IL-4-dependent Stat6 phosphorylation. By contrast, Socs3 was found to be a major regulator of IL-23-mediated Stat3 phosphorylation and Th17 generation, and Stat3 directly binds to the IL-17A and IL-17F promoters. We conclude that Socs3 is an essential negative regulator of IL-23 signaling, inhibition of which constrains the generation of Th17 differentiation.